2021
DOI: 10.1016/j.amsu.2021.102243
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists self-perceived role competence in prevention and containment of COVID-19: A cross-sectional study

Abstract: Introduction The increased need for prioritized infection prevention and control (IPC) activities for the prevention and containment of COVID-19 is pivotal and timely in preventing harm caused by the COVID-19 pandemic. Little is known about pharmacists' infection IPC activities and their role competence during disease outbreaks. This study aimed to assess pharmacists' perceived role competence to perform frontline roles during the COVID-19 pandemic. Method A cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For that reason, they chose social media, network news that appeared on TV sets, and online news media to collect the information concerned to COVID-19. Muflih et al (2021) found that 58.2% of their respondents used social media, and 25.3% used local and international channels for COVID-19 information. Their participants used these sources daily to weekly.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, they chose social media, network news that appeared on TV sets, and online news media to collect the information concerned to COVID-19. Muflih et al (2021) found that 58.2% of their respondents used social media, and 25.3% used local and international channels for COVID-19 information. Their participants used these sources daily to weekly.…”
Section: Discussionmentioning
confidence: 99%
“…The survey tool was developed based on the current literature on the role of CPs in responding to disasters and pandemics 14,15,[19][20][21][22] and Korean context. 12,23 For example, the questions in the response phase were developed considering Korean policy.…”
Section: Survey Developmentmentioning
confidence: 99%
“…The first section comprised (1) questions regarding the characteristics of CPs, including sex, age, work type (eg, pharmacy owner or pharmacy employee), pharmacy work experience, and working hours per day; (2) questions on whether the CP participates in outreach pharmaceutical services (eg, pharmacist home visit, drug safety use education, and safe pharmacy program) and frequently provides consultation and relevant information on the efficacy and side effects of over-the-counter (OTC) medicines; (3) questions about COVID-19 information resources (eg, government, KPA, academic journals or professional books, online newspapers, and Social Networking Service [SNS]) and the frequency of using these resources; and (4) questions regarding pharmacy characteristics, including pharmacy location, the total number of pharmacists working for the pharmacy, the total number of daily prescriptions dispensed at the pharmacy, and the total sales of OTC drugs per day. [20][21][22] The second section of the survey comprised questions regarding the importance and performance of the roles that the CPs recognized during the pandemic. The role of the CPs in the PPRR phases, reported in the study by Cadogan and Hughes, 14 were determined during the COVID-19 pandemic, and the specific roles were modified based on the situation in Korea.…”
Section: Survey Developmentmentioning
confidence: 99%